Micrometeoroid impact charge yield for common spacecraft materials. Issue 8 (18th August 2014) - Collette, A.; Grün, E.; Malaspina, D.; Sternovsky, Z.
Abstract The impact ionization charge yield is experimentally measured from four common materials used in space and specifically on the two STEREO spacecraft (germanium‐coated black Kapton, beryllium copper, multilayer insulation, and solar cells). Cosmic dust particle impacts on spacecraft have been detected by electric field and plasma and radio wave instruments. The accurate interpretation of these signals is complicated by many factors, including the details of the spacecraft antenna system, the local spacecraft plasma environment, and our understanding of the physics of the impact process. The most basic quantity, the amount of charge liberated upon impact, is generally considered poorly constrained and is suspected to depend on the target material. Here we show that for common materials used on spacecraft this variability is small for impacts around 10 km/s, and the impact charge yield can be approximated by 80 fC for a 1 pg projectile. At higher speeds (∼50 km/s), variation of up to a factor of 5 is observed. The measured yields in the 10–50 km/s range are compared to measurements and predictions from the literature and are found to be lower than predicted by at least a factor of 12 at 10 km/s and at least a factor of 1.7 at 50 km/s. Impact charge is also found to depend on angle of incidence; the data suggest a maximum at 45°.